2011
DOI: 10.1007/978-3-642-25873-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Response Time Bounds for G-EDF without Intra-Task Precedence Constraints

Abstract: Abstract. Prior work has provided bounds on the deadline tardiness that a set of sporadic real-time tasks may incur when scheduled using the global earliest-deadline-first (G-EDF) scheduling algorithm. Under the sporadic task model, it is necessary that no individual task overutilize a single processor and that the set of all tasks does not overutilize the set of all processors. In this work we generalize the task model by allowing jobs within a single task to run concurrently. In doing so we remove the requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…5.3). Similar to our work, analyses of scheduling algorithms that allow jobs within a single task to run concurrently are presented in [12,26]. However, both these works consider global scheduling algorithms which, as mentioned earlier, entail high overheads especially in distributed memory architectures.…”
Section: Related Workmentioning
confidence: 89%
See 2 more Smart Citations
“…5.3). Similar to our work, analyses of scheduling algorithms that allow jobs within a single task to run concurrently are presented in [12,26]. However, both these works consider global scheduling algorithms which, as mentioned earlier, entail high overheads especially in distributed memory architectures.…”
Section: Related Workmentioning
confidence: 89%
“…However, both these works consider global scheduling algorithms which, as mentioned earlier, entail high overheads especially in distributed memory architectures. In addition, in both [12] and [26] the potential of exploiting job parallelism to achieve higher energy efficiency is not explored.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we establish two results that enable prior work to be leveraged to establish response-time bounds for DAG-based task systems. First, we show that, under the obi-task model with arbitrary offset settings, per-task response-time bounds can be derived by exploiting prior work pertaining to a task model called the npc-sporadic task model ("npc" stands for "no precedence constraints"-this refers to the lack of precedence constraints among jobs of the same task) [14,27]. Second, we show that, by properly setting offsets, any DAG-based task system can be transformed to a corresponding obi-task system.…”
Section: Response-time Boundsmentioning
confidence: 99%
“…In devising such counterexamples, the goal is to ensure that a certain low-priority task is unable to make use of processors made available to it in parallel, thereby causing its response times to grow without bound. This relaxed task model has in fact been considered previously in work directed at using G-EDF in HRT [2] and SRT systems [10,12]. The latter work showed that allowing intra-task parallelism enables much lower tardiness bounds to be derived.…”
mentioning
confidence: 91%